1996
DOI: 10.1118/1.597736
|View full text |Cite
|
Sign up to set email alerts
|

Direct reading measurement of absorbed dose with plastic scintillators—The general concept and applications to ophthalmic plaque dosimetry

Abstract: We have developed dosemeters based on plastic scintillators for a variety of applications in radiation therapy. The dosemeters consist basically of a tissue-substituting scintillator probe, an optical fiber light guide, and a photomultiplier tube. The background light generated in the light guide can be compensated by a simultaneous measurement of the light from a blind fiber. Plastic scintillator dosemeters combine several advantageous properties which render them superior to other dosemeter types for many ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 0 publications
0
84
0
2
Order By: Relevance
“…Measurements on ophthalmic applicators ( 125 I and 106 Ru/ 106 Rh) showed a contribution of Cherenkov light of no more than 2%. This system has been used for measurements on both ophthalmic plaques [59] and intravascular brachytherapy sources [60][61][62]. The Optidos TM is a commercial version of this system developed by PTW (PTW Freiburg GmbH, Freiburg, Germany).…”
Section: Plastic Scintillatormentioning
confidence: 99%
“…Measurements on ophthalmic applicators ( 125 I and 106 Ru/ 106 Rh) showed a contribution of Cherenkov light of no more than 2%. This system has been used for measurements on both ophthalmic plaques [59] and intravascular brachytherapy sources [60][61][62]. The Optidos TM is a commercial version of this system developed by PTW (PTW Freiburg GmbH, Freiburg, Germany).…”
Section: Plastic Scintillatormentioning
confidence: 99%
“…As examples, de Boer and colleagues [6] performed spectral measurement of radiation-induced light in plastic scintillator dosimeters and investigated the feasibility of optical filtering for the stem effect subtraction. Flühs and colleagues [7] developed dosimeters based on plastic scintillators for a variety of applications in radiation therapy and, in particular, employed such systems for eye plaque dosimetric treatment optimization. Létourneau and colleagues [8] studied the properties of a miniature scintillating detector, suitable for small field radiation dosimetry, using a configuration similar to that of Beddar [4] for facing the limitation due to the stem effect.…”
Section: Introductionmentioning
confidence: 99%
“…This is the primary reason why plastic scintillators have been so extensively studied for use as in-situ real-time dosimetry probes for high-energy bremsstrahlung medical radiation treatment monitoring. 1,[6][7][8][9][10] Medical dosimetry research has shown common plastic scintillators to have water equivalent (tissue equivalent) energy deposition properties from 0.2 to 20 MeV, with the ratio of dose deposited in plastic to that deposited in water Dose Scintillator /Dose Water of about 0.98. 3,4,11,12 It is worth noting that most of the work cited here has involved placing small scintillators ( <1 cm 2 ) within the body or a water-equivalent phantom, therefore establishing a charge particle equilibrium (CPE) condition that satisfies the Bragg-Gray principle.…”
Section: Introductionmentioning
confidence: 99%